STUDIES ON THE LOCALIZATION OF CIRCULATING ANTIGEN-ANTIBODY COMPLEXES AND OTHER MACROMOLECULES IN VESSELS : II. PATHOGENETIC AND PHARMACODYNAMIC STUDIES - Cochrane, Charles G. (The Rockefeller University Press, 1963)
Localization of circulating antigen-antibody complexes in vessels of guinea pigs by means of anaphylactic shock was found to be mediated by histamine that was released at the time of anaphylaxis. The source of the histamine may have been the mast cell as noted in studies employing a direct attack on the mast cells by octylamine. Platelets played apparently little to no role in guinea pigs in the anaphylactic deposition of circulating complexes. Rat anaphylatoxin was found to cause vascular localization and symptoms of anaphylaxis identical with that brought about by antigen-antibody anaphylaxis. This also was found to be dependent upon the release of histamine. Antibody against Forssman antigen in the vessel walls of the guinea pigs also led to deposition of circulating complexes. This was found not to be histamine dependent. The possible role of local increase in vascular permeability in certain experimental disease states in the localization of circulating complexes is discussed.